Specjalne potrzeby edukacyjne ucznia z zespołem Renpenninga - wskazania praktyczne = Special educational needs of a pupil with Renpenning Syndrome - practical indications - Porada, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A pupil with a rare genetic disorder is a great challenge for the pedagogical community because they need specific support and early recognition of their needs; work with such a pupil undoubtedly requires going beyond the usual routine. If knowledge about a given developmental disorder is not complete, it is difficult to plan the correct therapeutic procedure and take care of the conditions for effective implementation of educational goals. One such disorder is Renpenning Syndrome, an X-linked disease caused by mutations in the PQBP1 gene. There is no cure for this syndrome and the frequency of its occurrence is unknown. Care for a child with Renpenning Syndrome is based mainly on early education and intervention by therapists and treatment of the remaining symptoms. This article is an attempt to summarise a year of work with a pupil with Renpenning Syndrome and propose strategies of conduct that may facilitate the teacher`s contact with such a pupil and indicate possibilities for planning better conditions for effective implementation of educational and therapeutic goals. The birth of a child with a rare genetic disorder does not necessarily mean that there is no prospect of their maximum development and functioning in society.
Keywords: zespół Renpenninga; choroba rzadka; choroba genetyczna; specjalne potrzeby edukacyjne; Renpenning syndrome; rare disease; genetic disease; special educational needs